Serine Protease Autotransporters of Enterobacteriaceae (SPATEs): Biogenesis and Function - Nathalie Dautin (Toxins, 2010)
Serine Protease Autotransporters of Enterobacteriaceae (SPATEs) constitute a large family of proteases secreted by Escherichia coli and Shigella. SPATEs exhibit two distinct proteolytic activities. First, a C-terminal catalytic site triggers an intra-molecular cleavage that releases the N-terminal portion of these proteins in the extracellular medium. Second, the secreted N-terminal domains of SPATEs are themselves proteases; each contains a canonical serine-protease catalytic site. Some of these secreted proteases are toxins, eliciting various effects on mammalian cells. Here, we discuss the biogenesis of SPATEs and their function as toxins.